2011
DOI: 10.1038/leu.2011.112
|View full text |Cite
|
Sign up to set email alerts
|

The absolute monocyte and lymphocyte prognostic score predicts survival and identifies high-risk patients in diffuse large-B-cell lymphoma

Abstract: Despite the use of modern immunochemotherapy regimens, almost 50% of patients with diffuse large-B-cell lymphoma will relapse. Current prognostic models, including the International Prognostic Index, incorporate patient and tumor characteristics. In contrast, recent observations show that variables related to host adaptive immunity and the tumor microenvironment are significant prognostic variables in non-Hodgkin lymphoma. Therefore, we retrospectively examined the absolute monocyte and lymphocyte counts as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
166
7
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(188 citation statements)
references
References 59 publications
(70 reference statements)
13
166
7
2
Order By: Relevance
“…Wilcox et al 19 first described the role of AMC/ALC prognostic score in diffuse large-B-cell lymphoma. Subsequent evidence also investigated the prognostic value of ALC/AMC prognostic score in diffuse large-Bcell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Wilcox et al 19 first described the role of AMC/ALC prognostic score in diffuse large-B-cell lymphoma. Subsequent evidence also investigated the prognostic value of ALC/AMC prognostic score in diffuse large-Bcell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…30,36,37 Antecedent evidence verified that ALC and AMC were parameters to predict outcomes in several types of cancer. [14][15][16][17][18][19][20][38][39][40][41][42] ALC and AMC have been studied as combined factors in Hodgkin's lymphoma and diffuse large B-cell lymphoma. 19,[21][22][23][24][25][26] Results showed that ALC/AMC ratio and AMC/ALC prognostic scores seemed to be associated with outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations